Receber em casa ou buscar no local? Um estudo das preferências dos consumidores de e-commerce - Cândido, Juliano Honorato (2021)
The growth of retail e-commerce numbers show that this purchase modal is very important in the global consumption pattern. However, this growth brings some challenges for managers in the logistical processes of traditional delivery, especially at the last delivery process, know as the Last Mile (LM), when the product leaves the warehouse and arrives at the consumers’ home. Problems such as deliveries failure and failure to attend the delivery deadline cause consumer dissatisfaction and therefore generate negative consequences for retailers. In this sense, one of the solutions presented by literatura is the Pick-up Point (PUP) Solution, where the consumer participates in the delivery process and pick-up the purchased product at the chosen establishment, instead of receiving at home, as in the traditional Home Delivery (HD) process. However, given the fact that the PUP Solution is still regarded as an innovative solution, it generates some degree of uncertainty and anxiety on part of the consumers. Therefore, some authors seek to understand which factors lead the consumers to choose PUP instead of HD. Still there is a gap in the literature about consumers sensitivity to changes at the level of these factors. So the goal of this dissertation was to observe which are the significant factors, the consumers’ sensitivity to changes at the level of these factors and the order of influence that these factors exert on the consumer’s preference for PUP over HD. In order to achieve this goal, the dissertation performed an design of experiment, using Stated Preference technique, to apply a survey that, after being applied to a sample of 405 respondents, had it’s results analyzed using a robust logistic regression model by clusters and by Transactional Costs Theory’ point of view. The results shows that the atributes that significantly influence consumer choice for PUP over HD were the Shipping Fee and Delivery Time. On the other hand, although the literature presents the Shipping Price as the most influential factor in most studies, the results here discussed show that Delivery Time was the most influential one. In addition, the results also showed that the PUP Location attribute wasn’t considered statistically influential in consumer choice for PUP over HD. Finally, the results of this dissertation show that the internal variation in levels of Shipping Price atributte has a greater impact on the consumers’ intention to use the PUP than the internal variation in the leves of the Delivery Time attribute.